What Policies Advance Infants and Toddlers? Evidence to Inform State and Federal Options. Issue 1 (13th April 2020) - Fuller, Bruce; Bridges, Margaret; Land, Austin
Abstract: A variety of civic actors—government, associations, and local agencies—work to help parents advance the vitality of our youngest children. Empirical findings accumulating over the past half‐century identify benefits for infants and toddlers stemming from three policy models: paid leave for parents after a newborn arrives; regular pediatric assessments, including home visiting; and quality caregivers situated in homes or centers. We review what is known about the effects of these policies, along with constituent elements of quality (mediators) that operate proximal to children's health, cognitive, and emotional growth. Much has been learned about how such collective action, carried out by local organizations, advance infant–toddler development. Methodological advances foster new knowledge: moving closer to causal inferences and pinpointing social mechanisms that enrich infant–toddler settings. Less well understood is how policy levers can move the malleable elements of program quality to raise the magnitude or sustainability of program effects. We note the benefits of income‐support efforts for fragile families, while urging new work on how economic dynamics touch the capacity of parents and caregivers to better nurture infants and toddlers.